Exploring Translation Strategies: A Content Analysis of the English Translation of the Holy Quran - Ur Rahman, Atta (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2023)
This study aims to diagnose culture-specific items (CSIs) in the English translation of the Holy Quran and the strategies used to translate the CSIs. Translating CSIs can be demanding because such items have specific meanings in the culture and language in which they exist but not necessarily in others. Considering this fact, the present study investigates the strategies used in the translation of culture-specific items in the English translation of the Holy Quran. To achieve these goals, the descriptive approach is applied to the analysis of the translation of specific items of culture. The descriptive analysis is also used to investigate the translation strategies used therein. The findings of this study indicate that the use of the cultural equivalent strategy was the most frequently applied strategy. The second most frequently applied translation strategies were the descriptive equivalent and thorough translation, followed by transference, functional equivalent, componential analysis, synonymy, modulation, and notes. The results show that the translation strategies are helpful (especially the target-oriented ones) in different ways to convey the meaning of the text from Arabic into English.